The design of future music technologies: ‘sounding out’ AI, immersive experiences & brain controlled interfaces - Chamberlain, Alan; Bødker, Mads; Kallionpää, Maria; Ramchurn, Richard; De Roure, David; Benford, Steve; Dix, Alan; Gasselseder, Hans-Peter (2018)
This paper outlines some of the issues that we will be discussing in the workshop “The Design of Future Music Technologies: ‘Sounding Out’ AI, Immersive Experiences & Brain Controlled Interfaces.” Musical creation, performance and consumption is at a crossroads, how will future technologies be affected by exciting and innovative new developments in artificial intelligence, immersive technologies and developing mechanisms for interfacing with music, such as Brain Controlled systems. In many respects this document acts as a mini survey, made up of supporting material, a bibliography of works and offers a series of quotes from work that has mainly emerged from the FAST Project – see: www.semanticaudio.co.uk.